Penguatan Karakter Peduli Lingkungan Peserta Didik melalui Program “Asri” di Sekolah Dasar - Airinan Prima Sabila; Ana Andriani (Universitas Muhammadiyah Mataram, 2026)
Abstract: Environmental care character among students currently shows a low condition. This study aims to describe the strengthening of students' environmental care character through the implementation of the ASRI Program (Safe, Cool, Neat, and Beautiful) at Piasa Wetan Public Elementary School. Another objective is to identify supporting factors, inhibiting factors in its implementation. The approach used in this study is a descriptive qualitative method. Data collection was carried out through observation, in-depth interviews with 4 informants consisting of 1 principal, 1 teacher, 1 student, and 1 school guard. The data analysis technique used an interactive model analytical descriptive method. The validity of the data was tested through credibility, triangulation, transferability, dependability, and confirmability. The results of the study indicate that character strengthening is carried out through routine morning hygiene habits, direct role models from teachers, regular socialization, local cultural innovations in the form of the slogan